The Effect of Financial Inclusion and Financial Literacy on The Performance of MSMEs Batik Wonogiren (Case Study on Batik MSMEs in Wonogiri Regency) - Widati, Sari; Putri, Gustita Arnawati; Arfiani, Rheysitta Dyah (RSF Conference Series: Business, Management and Social Sciences, 2023)
This study examines the effect of financial inclusion and financial literacy on the performance of Batik Wonogiren MSMEs. Wonogiren Batik comes from Wonogiri district, Central Java, Indonesia. The sample used in this study was 90 Wonogiren Batik MSMEs as respondents. The data collection method uses probability sampling techniques with questionnaires. The processed data was analyzed using multiple linear analysis techniques through the SPSS software program version 25.0 for Windows. The results of this study show that financial inclusion and financial literacy positively affect the performance of Batik Wonogiren MSMEs.